Impact of climate change on water availability for agricultural irrigation in Jaén, 2025 - Mejía Tucto, Mario Frankdux (2026)
The study assessed the impact of climate change on water availability for agricultural irrigation in Jaén Province, Cajamarca, during 2025. Research was conducted in the Amojú River basin, analyzing variations in precipitation, temperature, streamflow, and evapotranspiration under RCP4.5 and RCP8.5 climate scenarios. A regional hydrological model calibrated with historical data (2000–2020) was applied, and water demand was estimated for the main local crops: coffee, maize, cocoa, and rice. Results showed an annual average streamflow decrease of up to 20 % and a 30 % reduction in irrigation water availability under the RCP8.5 scenario, along with a 15 % increase in evapotranspiration. Simulated yield losses ranged between 10 % and 25 %, with rice and maize being the most affected crops. It is concluded that climate change poses a significant threat to water security and agricultural sustainability in the region, highlighting the need for integrated water management focused on improving irrigation efficiency and local climate adaptation.